Determinant of Thin Capitalization in Multinational Companies in Indonesia - Adi Nugroho; Trisni Suryarini (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
Thin capitalization is action of tax avoidance by having total debt more than total capital and that debt obtained from the same group of companies. This research aims to obtain the empirically evidence regarding the influence of multinationalism, tax haven utilization, tax uncertainty, firm size, and audit committee size against thin capitalization. The population in this research is multinational companies listed on the Indonesian Stock Exchange in the year of 2014-2016. The sampling technique was purposive sampling and got an analysis unit of 40 companies. Ordinal Least Square (OLS) with SPSS is used as the analytical technique. The results show that multinationalism, tax haven utilization, tax uncertainty, and firm size have a significant positive effect on thin capitalization. The results also prove that the size of audit committees has significantly negative effect on thin capitalization. This research concludes that thin capitalization is influenced by multinationalism, tax haven utilization, tax uncertainty, firm size, and audit committee size. Suggestions related to this research are for further research to ensure the measurement of tax uncertainty more objectively and to extend sampling time.